Implementasi Kebijakan Program Nasional Pemberdayaan Masyarakat Mandiri Pedesaan Di Distrik Sugapa Kabupaten Intan Jaya Provinsi Papua - Sondegau, Yulius (JURNAL ILMIAH SOCIETY, 2016)
The purpose of this research is to know the policy implementation national community empowerment program in rural independent Sugapa District Intan Jaya district of Papua province. To find out the results of the national community empowerment program in rural independent Sugapa District Intan Jaya district using basic survey with qualitative research. The research location is set in Sugapa District Office. Background of writing title policies regarding the implementation of the national program of rural self-empowerment, how important they were in the field through this program is based on sufficient capital to a good cause. why the program is not maximized. The factors that influence was lack of human resources, education levels are still low, inadequate number of staff empowerment and expertise to the lack of relations between the government in the District Sugapa as executor in the district with the district governments Intan Jaya as those under center in the area. Keywords: Policy Implementation,Community Empowerment